Nomogram to predict postoperative complications after cytoreductive surgery for advanced epithelial ovarian cancer: A multicenter retrospective cohort study - Jiang, Caixia; Liu, Yingwei; Tang, Junying; Li, Zhengyu; Min, Wenjiao (Frontiers in Oncology, 2022)
Objective: To establish and externally validate nomograms to predict the risk of postoperative complications after cytoreductive surgery for advanced epithelial ovarian cancer (AEOC) patients. Methods: A multicenter retrospective cohort study was designed, including patients with FIGO stage IIIC-IV epithelial ovarian cancer who underwent cytoreductive surgery. Patient preoperative characteristics were used to predict the risk of postoperative complications by univariate and multivariate analyses. Nomograms were developed based on multivariate modeling. Results: Overall, 585 AEOC patients were included for analysis (training cohort = 426, validation cohort = 159). The results showed that the incidence of postoperative overall and severe complications in the training cohort were 28.87% and 6.10%, respectively. Among the clinical variables assessed, modified frailty index (mFI) (OR 1.96 and 2.18), FIGO stage (OR 2.31 and 3.22), and Surgical Complexity Score (SCS) (OR 1.16 and 1.23) were most strongly associated with the risk of overall and severe complications, respectively. The final nomograms had superior internal discrimination with the C-index were 0.74 and 0.78 for predicting overall and severe complications, respectively, as well as good consistency and stable calibration. Additionally, the validation cohort suggested a good external discrimination with the C-index were 0.92 and 0.91 to predict overall and severe complications, respectively. Conclusions: Cytoreductive surgery for AEOC is at significant risk for the occurrence of substantial postoperative morbidity. These two nomograms can help clinicians to predict the risk of postoperative complications, and instruct clinical decision-making, as well as perioperative care to prevent adverse outcomes for AEOC patients.